2008
DOI: 10.1029/2008gl034160
|View full text |Cite
|
Sign up to set email alerts
|

Winter “weekend effect” in southern Europe and its connections with periodicities in atmospheric dynamics

Abstract: Winter weekly cycles of different climatic variables have been detected over Spain during the 1961–2004 period. The 13 analyzed series come from stations placed on different climatological and geographical areas with different level of urban influence. Therefore, the weekly cycles can hardly be related with local effects. Contrarily, we suggest that the weekly cycles may be related with changes in the atmospheric circulation over Western Europe, which may be due to some indirect effect of anthropogenic aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 23 publications
(37 reference statements)
5
64
2
Order By: Relevance
“…Bäumer et al, 2008), with maximum concentrations during central weekdays and minimum concentrations in the weekends. But while Sanchez-Lorenzo (2008) found corresponding weekly cycles in climate variables for 13 stations in Spain, their findings was later disputed by Hendricks Franssen et al (2009), who found no significant weekly cycles performing more rigorous statistical analyses of the same data. Similarly, Bäumer and Vogel (2007) found significant weekly cycles in temperature, cloud amount and precipitation for 12 stations in Germany, while Barmet et al (2009) performed a similar study of 17 stations in Switzerland and did not find statistically significant weekly cycles for any meteorological quantities.…”
Section: W Stjern: Weekly Cycles In Precipitation and Other Meteomentioning
confidence: 89%
See 1 more Smart Citation
“…Bäumer et al, 2008), with maximum concentrations during central weekdays and minimum concentrations in the weekends. But while Sanchez-Lorenzo (2008) found corresponding weekly cycles in climate variables for 13 stations in Spain, their findings was later disputed by Hendricks Franssen et al (2009), who found no significant weekly cycles performing more rigorous statistical analyses of the same data. Similarly, Bäumer and Vogel (2007) found significant weekly cycles in temperature, cloud amount and precipitation for 12 stations in Germany, while Barmet et al (2009) performed a similar study of 17 stations in Switzerland and did not find statistically significant weekly cycles for any meteorological quantities.…”
Section: W Stjern: Weekly Cycles In Precipitation and Other Meteomentioning
confidence: 89%
“…Gong et al, 2007;Jin et al, 2005;Marr and Harley, 2002) and provide an interesting approach to search for anthropogenic effects on climate, as no natural process with a constant cycle of 7 days over long time periods is know to exist (Sanchez-Lorenzo et al, 2008). Yet studies of weekly cycles in meteorological parameters yield highly contrasting results (Schultz et al, 2007), most likely due to a combination of varying statistical methods and the above mentioned non-linearity of the aerosol-precipitation effects.…”
Section: W Stjern: Weekly Cycles In Precipitation and Other Meteomentioning
confidence: 99%
“…Gong et al, 2006;Choi et al, 2008b;). On the other hand, even more uncertainties exist in Europe as there is no general consensus about the reliability of studies suggesting significant WCs (Bäumer and Vogel, 2007;Sanchez-Lorenzo et al, 2008), as well as there is a greater proportion of studies rejecting the existence of significant WCs. A possible WC in temperature is still likely, as there are significant results for different European countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In several papers (e.g. Bäumer and Vogel, 2007;Sanchez-Lorenzo et al, 2008;Kim et al, 2009) 3. It is also important to realize that tests which did not result in a significant WC were in general not published in the scientific literature, whereas significant WCs are much more likely to have been published.…”
Section: Weekly Cycles Dilemma: a Statistical Talementioning
confidence: 99%
See 1 more Smart Citation